The Sribasuki Community's Interpretation of the Economic Role of Women in Micro Enterprises - Putra, Dimas Arya; Janani, Ilham Riyad; Arivani, Vika; Akbar Maulana Putra; Wellfarina Hamer (Al Huwiyah: Journal of Woman and Children Studies, 2025)
This study examines women's contribution to the family economy through micro-enterprises in Sribasuki Village and how the community perceives this economic role. In the context of a rural society that still holds strong traditional values, the urgency of this research arises because women's economic contributions are often not appreciated proportionally. The objectives of this study are to analyze the community's perception of women's role in micro-enterprises, identify the forms of their contributions, and reveal the obstacles they face. The research uses a descriptive qualitative approach with data collection techniques of in-depth interviews, participatory observation, and documentation of five key informants. The results show that women not only contribute financially through culinary and handicraft businesses, but also play a strategic role in household financial management and meeting the basic needs of the family. Involvement in microenterprises increases women's independence, self-confidence, and bargaining power in family decision-making, indicating a shift in public perception. However, women still face structural obstacles such as limited capital, market access, and business literacy. As a result, systematic empowerment programs are needed, including training, access to inclusive financing, and network strengthening to optimize women's economic contribution potential.